Sprint-Up: A new device for sprint and change of direction training in footballers - Salerno, P.; Zanetti, C. (Sport Performance & Science Reports, 2020)
Resisted sled sprint training has proven effective in improving sprint. In recent years the focus has shifted more to horizontal force generation against relatively heavy loads.The idea is also developing that sprint training can be a kind of vaccine against Hamstring injuries. Sprint training iscomplex: it has been shown that, especially in adulthood andin already well-trained athletes, despite some of them spending years training sprint, performance often improves little over short distances. Generally, the peaks in sprint performance are reached between 20-28 years of age. A fundamental component of the athletic performance of the footballeris the change of direction, a motor skill that requires a considerable mechanical component characterized by accelerationand deceleration phases.